Functional coordination of the activities of consulting and engineering companies with the main stakeholders of a construction development project - DRUZHYNIN, Maksym; IVANYNA, Oleksandr; KOLOMIIETS, Valerii; BUBON, Sergii (Ways to Improve Construction Efficiency, 2025)
Functional coordination of the activities of consulting and engineering companies with the key stakeholders of a construction development project is a crucial factor in ensuring the efficiency, predictability, and sustainability of its implementation. In the context of a dynamic real estate market, the complexity of development projects is increasing, which requires the involved parties not only to possess professional expertise but also the ability to integrate and manage strategically. Modern construction processes involve a wide range of participants, including developers, investors, contractors, government regulators, public organizations, and end consumers. The interconnections between these entities must be clearly structured, which necessitates the involvement of professional intermediaries in the form of consulting and engineering companies. Consulting companies play a leading role in defining the project strategy, analyzing market risks, financial planning, and providing legal support for transactions, while engineering companies offer technical expertise, innovative solutions, and quality control of work performance. Their effective interaction with project stakeholders helps minimize costs, shorten construction timelines, and enhance the resilience and competitiveness of the development product. Optimizing communication processes between these companies and key project participants requires the development of flexible management mechanisms, including the use of digital platforms, integrated document management systems, and risk forecasting analytical tools. A key aspect of functional coordination is managing conflicts of interest that arise during decision-making. The presence of institutional and regulatory mechanisms that govern the distribution of responsibilities among participants helps improve the transparency of development processes and strengthens trust between the parties. The implementation of sustainable construction concepts, which consider environmental, social, and economic factors, is also important as it promotes the harmonization of interactions between public and private institutions. Research into the functional coordination of consulting and engineering companies within construction development projects enables the development of effective management models that contribute to cost optimization, enhanced project implementation quality, and the strengthening of developers’ market positions. The development of this field is an integral part of the transformation of the construction sector amid increasing competition and digitalization of the economy.